Penerapan Teknologi Tepat Guna Untuk Pengelolaan Sampah KRL Berani Asri Duta Mekar Asri Cileungsi Bogor - Prayudi Suparmin; Roswati Nurhasanah; Hendri Hendri; Arief Suardi Nurchairot (Sekolah Tinggi Teknik - PLN, 2020)
Green Village (KRL) is one of the programs to realize Bogor Green and Clean Regency. KRL Berani Asri RW 15 Cileungsi Kidul was formed to carry out the production, management and utilization independently. Has several problems such as environmentally friendly awareness, not yet optimal waste management, the economic potential of organic and non-organic waste. P2M Mechanical Engineering Study Program IT PLN aims to provide alternative solutions so that KRL Berani Asri is independent in waste management. The method of implementation is socialization, training on waste management, composting, and making plastic chopper machines. The results of the P2M are 67.8% of resident have knowledge about waste management, 61.7% have good waste management behaviour, and 53.8% of residents say that KRL Berani Asri does not yet have waste management infrastructure. The use of appropriate technology has an impact on increasing compost production from 50 bags to 200 bags per week, and the production of plastic that has been sold from 10 kg to 100 kg per week